A multifaceted evaluation of hybrid energy policies: The case of sustainable alternatives in special Economic Zones of the China Pakistan Economic Corridor (CPEC) - Bilal, Muhammad; Ali, Muhammad Khurram; Qazi, Usama; Hussain, Salman; Jahanzaib, Mirza; Wasim, Ahmad (Sustainable energy technologies and assessments, 2022)
[Display omitted] •Sustainability potential of Special Economic Zones is revealed.•Sustainable policies are ranked using Multicriteria Decision Making.•High investment costs of smart energy solutions can be coped.•Hybrid solutions having smart devices secured top ranks in most of the zones. While the gradual switch over to sustainable energy generation is under the limelight around the globe, developing nations are still struggling to meet their basic demand-supply deficits, which leads them to adopt short-term solutions like burning fossil fuels. Although the proposed mega-transportation project of the China Pakistan Economic Corridor (CPEC) is subject to background political concerns, it has a strong potential to become a launching pad for sustainable energy growth in Pakistan. This study offers a multi-criteria decision-making (MCDM) approach for real-world prioritization of sustainable hybrid energy policy alternatives in the Special Economic Zones, planned as a constituent of the CPEC project. The factors affecting the energy policies are rigorously explored, screened, and prioritized. Flexible hybrid policy alternatives are designed with respect to the local situation in the respective economic zones. The problem is modeled using MCDM methodologies and solved by taking real-world data into account. Alternatives involving hybrid renewable solutions with sophistication in technology secure the highest positions in the ranking for most of the zones. The research outcomes, in the form of these prioritized sustainable energy policy rankings, are highly attractive for all the stakeholders, including global investors and national and international policy makers.